Seafood and omega-3s for maternal and child mental health - Newton, Wendy; McManus, Alexandra (Quay Books Division, 2013)
This chapter focuses on seafood and omega-3 fatty acids for maternal and child mental health with particular emphasis on the role of maternal, gestational and childhood nutrition. The inclusion of seafood within a health diet, in conjunction with current best practice treatments, has the potential to significantly impact the burden of disease attributable to mental health disorders.